PROGRAMA DE ATENÇÃO AO IDOSO: CONDIÇÕES DE SAÚDE E CAPACIDADE FUNCIONAL DOS IDOSOS - Mafalda, Aline; Berlezi, Evelise M.; Eickhoff, Heloisa M.; Oliveira, Karla R. d.; Dallepiane, Loiva B.; Perlini, Nara M. O. G. (Salão do Conhecimento, 2013)
Resumo